Relation between density and compressive strength of foamed concrete - Rokiah, Othman; Putra Jaya, Ramadhansyah; Khairunisa, Muthusamy; Mohd Arif, Sulaiman; Youventharan, Duraisamy; Mohd Mustafa Al Bakri, Abdullah; Przybył, Anna; Sochacki, Wojciech; Skrzypczak, Tomasz; Vizureanu, Petrica; Sandu, Andrei Victor (MDPI AG, Basel, Switzerland, 2021)
This study aims to obtain the relationship between density and compressive strength of foamed concrete. Foamed concrete is a preferred building material due to the low density of its concrete. In foamed concrete, the compressive strength reduces with decreasing density. Generally, a denser foamed concrete produces higher compressive strength and lower volume of voids. In the present study, the tests were carried out in stages in order to investigate the effect of sand–cement ratio, water to cement ratio, foam dosage, and dilution ratio on workability, density, and compressive strength of the control foamed concrete specimen. Next, the test obtained the optimum content of processed spent bleaching earth (PSBE) as partial cement replacement in the foamed concrete. Based on the experimental results, the use of 1:1.5 cement to sand ratio for the mortar mix specified the best performance for density, workability, and 28-day compressive strength. Increasing the sand to cement ratio increased the density and compressive strength of the mortar specimen. In addition, in the production of control foamed concrete, increasing the foam dosage reduced the density and compressive strength of the control specimen. Similarly with the dilution ratio, the compressive strength of the control foamed concrete decreased with an increasing dilution ratio. The employment of PSBE significantly influenced the density and compressive strength of the foamed concrete. An increase in the percentage of PSBE reduced the density of the foamed concrete. The compressive strength of the foamed concrete that incorporated PSBE increased with increasing PSBE content up to 30% PSBE. In conclusion, the compressive strength of foamed concrete depends on its density. It was revealed that the use of 30% PSBE as a replacement for cement meets the desired density of 1600 kg/m3 , with stability and consistency in workability, and it increases the compressive strength dramatically from 10 to 23 MPa as compared to the control specimen. Thus, it demonstrated that the positive effect of incorporation of PSBE in foamed concrete is linked to the pozzolanic effect whereby more calcium silicate hydrate (CSH) produces denser foamed concrete, which leads to higher strength, and it is less pore connected. In addition, the regression analysis shows strong correlation between density and compressive strength of the foamed concrete due to the R2 being closer to one. Thus, production of foamed concrete incorporating 30% PSBE might have potential for sustainable building materials.